Development of physical fitness among the top 10 boys and girls in sport schools: a 10-year cohort analysis - Roth, A.; Schmidt, S. C. E.; Hartmann, S.; Seidel, I.; Scharenberg, S.; Bös, K. (Sports, 2019)
In this study, we aimed to measure the development of physical fitness (PF) of 10 different cohorts in grade 4 and 8 different cohorts in grade 7 at 18 sport schools of North Rhine-Westphalia, Germany. A total of 11,451 subjects (3979 female, 7472 male) aged 8-12 from the past 10 years were assessed using the German Motor Test (DMT) in grade 4. We tested 2614 subjects (1032 girls, 1582 boys) aged 11-15 from the past eight years using the DMT in grade 7. PF talents were defined as the top 10 boys and top 10 girls of each cohort. Linear regression was calculated to assess the development of PF. The PF of all subjects remained stable in grade 4 and declined in grade 7. The PF of the top 10 boys and top 10 girls increased in both grades. The improvements were stronger in grade 7 (female: rates of change (ß) = 0.80; male: ß = 0.76) than in grade 4 (female: ß = 0.36; male: ß = 0.32). Sit-ups and push-ups showed the highest change rates. The increase in PF of the top 10 boys and girls can be interpreted as a success for sport schools. Due to the increasing number of test participants, the likelihood of finding top talent increased. However, the increase in PF in the top talents was only partly explained by an increase in the number of tested individuals.